Measuring students' interest towards engineering in technical school: A case study - Radzi N.A.M.; Sulaiman S. (OmniaScience, 2023)
Estimating from the steady declining rate of engineering students in Malaysia, the country is predicted to be short of 236,000 engineers and technical personnel to achieve its 2020 Mission. Hence, it has built the first technical MARA Junior Science College that introduced engineering to lower secondary students. However, there is yet a study on whether or not it helps the students to increase their interests in engineering. Therefore, in this paper, a survey has been conducted to first and foremost investigate the technical students' interests in engineering as well as finding out the reasoning from those who are not interested in engineering. After that, a half day engineering program is introduced with a measurement on the interest in engineering before and after the intervention is held. Finally, the survey studies which field of engineering the students are most interested in. The results show that, before the program is introduced, only 8.47% of the technical students have shown high interests in engineering field with only 7.5% female students are interested in engineering compared to 18.42% for male students. After the program is introduced, as high as 33.05% students rated their interest in engineering field as 'most interested', with 39.47% in male students and 30% in female students. It proves that an engineering event is crucial in increasing students' interests in engineering. It also concludes that Electrical Engineering is the most favourite field of engineering with percentage score of 38.98%, while Electrical Power being the least. 2018 OmniaScience.